(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Longitudinal, shear ultrasonic speeds and constriction were estimated in various organizations of the glass frameworks of 20Na2O-(80-x) B2O3-x Li2O and 20Na2O-(80-x) B2O3-xWO3 (where x = 0 to 10 in ventures of 2 mol) at room temperature by utilizing pulser-recipient system at 5MHz. The glass tests were set up by ordinary dissolve extinguishing technique. The shapeless idea of the examples were found out utilizing X-beam diffractometry (XRD). The thickness of the glass tests was estimated with relative estimation strategy. The deliberate exploratory qualities are used to assess versatile moduli, Poisson’s proportion, acoustic impedance, inside erosion, microhardness, Debye temperature, and warm extension coefficient. Patterns of the coordination number, cross-interface thickness, mechanical and warm soundness for the frameworks are talked about as far as the basic changes occurring because of varieties in structure.